EFEKTIVITAS MEDIA MAGIC BOARD UNTUK MENGATASI KESULITAN BERHITUNG MATERI PEMBAGIAN PADA SISWA KELAS III SD NEGERI 1 BANYUKEMBAR KABUPATEN WONOSOBO - Putri Refi Mariska Aeshurga; Ahmad Khoiri; Vava Imam Agus Faisal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This Study was motivated by students’ low arithmetic ability in division material, as indicated by learning outcomes below the minimum mastery criteria (MMC) and difficulties in understanding division concepts. The purpose of this study was to determine the effectiveness of magic board media in overcoming difficulties in learning division among third-grade students at SD Negeri 1 Banyukembar, Wonososbo Regency. This study employed a quantitative approach using a pre-experimental method with a one group pretest-posttest design. The participants consisted of 30 third-grade students. Data were collected through tests, observation, and documentation, and analyzed using validity, reliability, normality testing, homogeneity testing, paired sample t-test, and N-Gain analysis. The result showed that student mean score increased from 50.83 in the pretest to 79.66 in the posttest. The number of students achieving the minimum mastery criteria increased from 4 students to 26 students the paired sample t-test revealed a significance value of 0,000 < 0,05, indicating a significant difference between pretest and posttest scores. Furthermore, the average N-Gain score was 0,6165 with an affectiveness percentage of 61.65%, categorized as quite effective. Therefore, magic board media is quite effective in helping students overcome arithmetic difficulties and improve their ability in division material at the elementary school level.